Pengembangan Media Buku Cerita Bergambar Berbasis Flipbook Digital pada Mata Pelajaran IPAS Kelas V SDN Purwoyoso 04 - Ainun, Sindy; Putra, Galih Mahardika Christian (FONDATIA, 2024)
This study aims to develop Digital Flipbook-Based Picture Storybook media as an effort to improve the learning outcomes of fifth grade students of SDN Purwoyoso 04 in IPAS subjects. The type of research method used is Research and Development (RnD) with a research design referring to the Borg and Gall model which is applied in this study until the eighth research stage of the ten stages of implementation. Data collection was carried out through test techniques in the form of pretests and posttests and non-test techniques in the form of interviews, questionnaires and documentation and using qualitative and quantitative data analysis techniques. The subjects in this study were 28 fifth grade students as large group product trials with sampling techniques, namely saturated sampling techniques and 6 fifth grade students as small group product trials with purposive sampling techniques. The results of this study are 1) the development of a Digital Flipbook-Based Picture Story Book media design developed based on the needs of teachers and students in learning, 2) the feasibility of this media gets a percentage value of 95% from media experts with the criteria “very feasible” and a percentage value of 89% from material experts with the criteria “very feasible”, and 3) the effectiveness of this media shows that there is an increase in student learning outcomes with an average pretest to posttest score of small group product trials of 35 (53 increased to 88) with an N-gain value of 0.7382 with “high” criteria and an increase in the average pretest to posttest score of large group product trials of 35 (55 increased to 90) with an N-gain value of 0.7948 with “high” criteria. The results obtained from the use of Digital Flipbook-Based Picture Storybook Media have a high effectiveness value on improving the learning outcomes of fifth grade students of SDN Purwoyoso 04 in IPAS subjects.